2016
DOI: 10.1002/nme.5456
|View full text |Cite
|
Sign up to set email alerts
|

A domain coupling method for finite element digital image correlation with mechanical regularization: Application to multiscale measurements and parallel computing

Abstract: To cite this version:Robin Bouclier, Jean-Charles Passieux. A domain coupling method for finite element digital image correlation with mechanical regularization: Application to multiscale measurements and parallel computing. International Journal for Numerical Methods in Engineering, Wiley, 2017, 111 (2) SUMMARYA general method is proposed to couple two sub-regions analysed with finite element digital image correlation (FE-DIC) even when using a mechanical regularization (R-DIC). A Lagrange multiplier is intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 46 publications
(126 reference statements)
0
20
0
Order By: Relevance
“…It can be observed that, when the beam moves on the left, the displacement is noisy (displacement is amplified by a factor 30) for 2 of the 9 images. Note that this issue could have been avoided by using larger elements or any other regularization technique [30,27,31,11] but it was allowed to persist as it enabled the effect of noise on mode measurement, to be visualized. The 7 other displacements were far less noisy.…”
Section: Incremental Dic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…It can be observed that, when the beam moves on the left, the displacement is noisy (displacement is amplified by a factor 30) for 2 of the 9 images. Note that this issue could have been avoided by using larger elements or any other regularization technique [30,27,31,11] but it was allowed to persist as it enabled the effect of noise on mode measurement, to be visualized. The 7 other displacements were far less noisy.…”
Section: Incremental Dic Analysismentioning
confidence: 99%
“…In this paper we propose to prescribe time-smoothness as a physical regularization technique in the space domain. This technique should not be opposed to existing space regularization methods [20,30,31,28,11,33], but should be rather seen as an additional tool, which can positively complement more conventional remedies. More precisely, the method starts from a space-time formulation of DIC [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…The proposed new algorithms for global (or FE) DIC may prove useful particularly (i) for evolution problems, where one operator is assembled and factorized once for all Gauss‐Newton iterations and for each time step, and (ii) for stereo DIC, where projector gradients may evolve during iterations. To go even further in algorithmic efficiency, these solvers could be coupled with high‐performance computing tools …”
Section: Resultsmentioning
confidence: 99%
“…To go even further in algorithmic efficiency, these solvers could be coupled with high-performance computing tools. 35,[44][45][46][47] ORCID Jean-Charles Passieux https://orcid.org/0000-0001-8387-4122 Robin Bouclier https://orcid.org/0000-0002-6265-4726…”
Section: Resultsmentioning
confidence: 99%
“…The expanding use of finite elements (FE) meshes in digital image correlation (DIC) algorithms is explained by their ability to be coupled with numerical models. The interaction of measurement and simulation becomes fast and friendly, as both kinematic fields are defined at the nodes of the same mesh.…”
Section: Introductionmentioning
confidence: 98%